Peningkatan Kinerja Inventory Planning pada Mitra 10 Melalui Pelatihan Demand Planning Management - Yuli Evitha; Cundo Harimurti; I Nyoman Purnaya; Resista Vikaliana (Institut Ilmu Sosial dan Manajemen Stiami, 2018)
Companies such as PT Mitra 10, in a competitive business world, need the role of the right business strategy, especially in supply-demand. Therefore, to avoid unbalanced supply-demand conditions, it is necessary to do supply-demand planning which always starts from demand planning. Planning that prioritizes demand in determining the amount of supply will produce a more balanced supply-demand condition than providing supply without prioritizing demand.Partner Company 10 requires superior HR competencies, to implement demand planning in its business processes. This competency is needed so that every HR is reliable in carrying out demand planning. Training is one of the ways expected to improve HR competencies.Demand Planning Management training is considered capable of being a solution to partner problems. The training was also considered capable of meeting the needs of Partner 10, with the aim of providing participants with techniques and methods for effective and integrated logistics management, which included purchasing, warehousing, inventory control and distribution of goods. This training is expected to improve the performance of PT Mitra 10.